Institutional promotion of research in Humanities and Social Sciences in Spain: SINC news agency of the Spanish Science and Technology Foundation-FECYT - López-Cantos, Francisco (Estudios sobre el Mensaje Periodístico, 2022)
For a few decades now, the general finding of the decline of “humanistic” areas of knowledge in most countries has been recurrent, while guided teaching and research around disciplines understood as more “scientific”—particularly those grouped in the STEM area and those related to Health and Biomedicine— have become increasingly popular. The widespread perception of the low utility and social application of humanistic knowledge, as well as its lack of scientific rigor, is not only common among citizens but also very prevalent among the research community, especially in the design of institutional policies for the social promotion of knowledge and scientific culture. In this study, we analyze the communicative strategy of research promotion at SINC news agency, as a sample of the institutional policies that are promoted by the Spanish public institutions in relation to the Humanities and Social Sciences areas. To this end, we use a methodological strategy that combines the quantitative and qualitative analysis of the contents understood as “humanistic” published in SINC and compare it with a sample of those perceived as more “scientific.” The results of the analysis confirm the low institutional interest in the promotion of “humanistic” knowledge by the SINC news agency of the Spanish Science and Technology Foundation (FECYT).